Wearable technology to characterize and treat mild traumatic brain injury subtypes: Study protocol for a randomized controlled trial on biofeedback-based precision rehabilitation (SuBTyPE) - Jae W. Lee; Prokopios Antonellis; Peter C. Fino; Robert J. Peterka; Jennifer L. Wilhelm; Kathleen T. Scanlan; Margaret E. Stojak; Jennifer L. Brodsky; Cecilia Monoli; Angela R. Weston; William Liu; Kody R. Campbell; et al. (PLoS ONE, 2026)
Background Rehabilitation of persistent imbalance in people with mild traumatic brain injury (mTBI) is challenging, and responsiveness to rehabilitation is often suboptimal. One reason for suboptimal outcomes may be patient heterogeneity within rehabilitation referrals. Specifically, people with greater vestibular and/or ocular-motor (V/O) symptoms may respond better to vestibular rehabilitation therapy (VRT) compared to those with greater mood or cognition symptoms. Poor performance of exercises may also explain suboptimal outcomes. This study aims to 1) assess if a wearable sensor-based multidimensional biofeedback system could enhance rehabilitation, 2) examine responsiveness to rehabilitation depending on the severity of V/O deficits, 3) characterize the impact of V/O deficits on gait and turning during seven days of unsupervised daily living and establish normative mobility data from active-duty service members. Methods This study is a single-blinded randomized controlled trial involving 100 individuals experiencing persistent symptoms from subacute and chronic mTBI. Participants will be randomized into VRT with or without sensor-based biofeedback. Both groups will receive a 6-week VRT. All participants will be tested for balance, gait, turning, and V/O performance before and after VRT. We will compare the efficacy of VRT with or without biofeedback, stratified by the severity of V/O symptoms. Additionally, a subset of 50 participants with mTBI and 40 healthy active-duty service members will wear inertial sensors for seven days to quantify daily mobility. We will use the data to examine if the severity of V/O deficits following mTBI impacts daily mobility and to establish normative data for daily living mobility from military service members. Discussion This study will be the first clinical trial to investigate whether wearable technology can improve rehabilitation outcomes for those with V/O symptoms by providing real-time biofeedback during rehabilitation. This work will also help to identify individuals with sensorimotor deficits associated with V/O subtypes. These results will enhance the assessment and rehabilitative care following mTBI by integrating objective measures to identify and address V/O subtypes. Furthermore, establishing normative data for daily living mobility from service members will aid in return-to-duty decision making following mTBI. Trial registration This protocol is registered on ClinicalTrials.gov under the number NCT06381674. Registered on April 04, 2024. Recruited period from June 2024 to September 2028. https://clinicaltrials.gov/study/NCT06381674 . Trial Protocol v1 (Dated November 14, 2023)